1634. A 9-Point Risk Assessment for Patients Who Inject Drugs Requiring Intravenous Antibiotics May Allow Health Systems to Focus Inpatient Resources on Those at Greatest Risk of Ongoing Drug Use. (26th November 2018) - Eaton, Ellen; Mathews, Ronald; Lane, Peter S; Paddock, Cayce S; Rodriguez, J Martin; Taylor, Benjamin B; Saag, Michael; Kilgore, Meredith; Lee, Rachael
Abstract: Background: We implemented an Intravenous Antibiotics and Addiction Team (IVAT) intervention to identify hospitalized persons with a history of injection drug use (IDU) that are safe for discharge with IV antibiotics based on a 9-point risk assessment. IVAT has been shown to reduce average length of stay (ALOS) without increasing readmissions. We analyzed the cost savings of the IVAT to the health system. Methods: PWID at the University of Alabama at Birmingham (UAB) hospital with indications for prolonged IV antibiotics received IVAT to determine risk of continued IDU. "Low-risk" patients were discharged for outpatient antibiotics and addiction care; others continued inpatient antibiotics, group therapy, opioid agonist therapy (if applicable), and weekly assessment for discharge readiness. Cost of care was defined by direct costs and was obtained by querying financial accounts. Results: A total of 37 pre-IVAT and 111 post-IVAT admissions (including 25 "low risk") met study criteria. IVAT reduced ALOS by 20 days. Total direct costs per admission in the post-IVAT period were 33% lower: $26, 014 versus $38, 716 (Table 1). Because ALOS at UAB for all patients is 6.58 days, a 20-day ALOS reduction following IVAT creates capacity for an additional 333 patients ( n = 20/6.58 × 111). Conclusion: IVAT for PWID allows health systems to focus inpatient resources on those at greatest risk of ongoing IVDU, creates additional inpatient capacity, and may cut hospital direct costs by one-third. Disclosures: J. M. Rodriguez, finch: Research Contractor, Research support. seres: Research Contractor, Research support.